Design of transtibial mechanical prosthesis with feedback to ground irregularities - Sebastian Contreras Marquez, Juan; Cifuentes-De la Portilla, Christian (2021 IEEE 2nd International Congress of Biomedical Engineering and Bioengineering (CI-IB&BI), 2021)
Most of the mechanical prostheses available do not have many of the important characteristics of the foot, such as flexibility, mobility and the ability to adapt to any type of terrain. Furthermore, as it is an artificial extension, people do not have sensory control over it and terrain adaptation depends entirely on the design of the prosthesis. This document proposes the design of a transtibial mechanical prosthesis capable of adapting to uneven terrain that will provide the user with feedback when a slope is detected. The proposed design is based on state-of-the-art functional models that are based on the shape and mobility of the human foot. The adaptability to uneven ground depending on the plantar mobility of the foot given by an ankle joint placed in the prosthesis. This plantar mobility allows to feedback about the level of inclination of the terrain through the use of sensors and actuators that transmit stimuli to the person's stump with information about different inclination conditions. The prosthesis also has two shock absorbers that help distribute the load when the heel strike occurs, these are made of fiberglass that has properties close to carbon fiber. The sole of the foot is flexible enough to adapt to small irregularities in the terrain. Additionally, this design features an ankle joint in order to emulate the kinematics of heel strike and toe-off that occurs during gait. The entire prosthesis, except for the shock absorbers, was created in 3D printing using PLA as a material, which facilitated and economized its manufacture. During the experimental tests this design proved to be functional subject to future improvements.